2004
DOI: 10.1023/b:pham.0000041465.89254.05
|View full text |Cite
|
Sign up to set email alerts
|

Role of PEPT2 in the Choroid Plexus Uptake of Glycylsarcosine and 5-Aminolevulinic Acid: Studies in Wild-Type and Null Mice

Abstract: Purpose. To determine the importance of PEPT2 in the uptake of glycylsarcosine (GlySar) and 5-aminolevulinic acid (5-ALA) in mouse choroid plexus whole tissue. Methods. Uptake studies were performed in bicarbonate artificial cerebrospinal fluid buffer using choroid plexuses isolated from PEPT2 +/+ and PEPT2 −/− mice. Results. PEPT2−/− mice exhibited a 90% reduction in GlySar uptake (p < 0.001) and a 92% reduction in 5-ALA uptake (p < 0.001) as compared to wild type animals. At 4°C (vs. 37°C), GlySar uptake wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Reinforcing this finding were the 2-fold greater CSF concentrations and 4-fold greater CSF/blood and AUC CSF /AUC blood ratios of GlySar in PEPT2 Ϫ/Ϫ mice, indicating that PEPT2 activity at the BCSFB reduces the exposure of GlySar in CSF. Thus, it was concluded that PEPT2 operates in vivo as an efflux transporter at the BCSFB, as suggested previously from in vitro studies on the choroid plexus uptake of GlySar and 5-aminolevulinic acid (Ocheltree et al, 2004a), carnosine (Teuscher et al, 2004), and cefadroxil (Ocheltree et al, 2004b) in transgenic mice. This conclusion is in complete accordance with the current model of peptide/mimetic trafficking at the BCSFB .…”
Section: Discussionsupporting
confidence: 67%
“…Reinforcing this finding were the 2-fold greater CSF concentrations and 4-fold greater CSF/blood and AUC CSF /AUC blood ratios of GlySar in PEPT2 Ϫ/Ϫ mice, indicating that PEPT2 activity at the BCSFB reduces the exposure of GlySar in CSF. Thus, it was concluded that PEPT2 operates in vivo as an efflux transporter at the BCSFB, as suggested previously from in vitro studies on the choroid plexus uptake of GlySar and 5-aminolevulinic acid (Ocheltree et al, 2004a), carnosine (Teuscher et al, 2004), and cefadroxil (Ocheltree et al, 2004b) in transgenic mice. This conclusion is in complete accordance with the current model of peptide/mimetic trafficking at the BCSFB .…”
Section: Discussionsupporting
confidence: 67%
“…2), as reported previously (25) after intravenous administration. 14 C-Gly-Sar was reported to be mainly excreted in urine (8), and 11 C-Gly-Sar was rapidly accumulated in the bladder (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…PEPT2 also transports various peptides and peptidemimetics (5). One of the peptide-mimetics, 5-aminolevulinic acid, which has been used as a photosensitizer and also to guide the surgical resection of glioblastoma multiforme (6), is a substrate of PEPT1 (7) and PEPT2 (8). Antitumor agent ubenimex ((2)-N-[-(2S,3R)-3-amino-2-hydroxy-4-phenylbutyryl]-L-leucine), which induces apostosis in glioma (9), is also a substrate of PEPTs (10).…”
mentioning
confidence: 99%
“…Contrary to the situation at the BBB, several lines of evidence indicate that members of the PTR family of proton-coupled peptide transporters are expressed at the BCSFB; this includes PEPT2, which is expressed in the CP membranes [173] and PHT1 [174] (Figure 3B). PEPT2 is a proton-coupled oligopeptide transporter and it is abundant in epithelial layers, including kidney, where it plays an important role in renal reabsorption of di- and tri-peptides [138,175].…”
Section: Molecular Biology Of Transport Processes Between Blood and Bmentioning
confidence: 99%